2020
DOI: 10.3390/jcm9103087
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Lifestyle-Modification in Patients with Ulcerative Colitis–A Randomized Controlled Trial

Abstract: Patients with ulcerative colitis suffer from impaired health-related quality of life (HrQoL). Comprehensive lifestyle-modification might increase HrQoL and decrease disease activity. Ninety-seven patients in clinical remission with impaired HrQoL were randomly assigned to a 10 week comprehensive lifestyle-modification program (LSM; n = 47; 50.28 ± 11.90 years) or control (n = 50; 45.54 ± 12.49 years) that received a single workshop of intense training in naturopathic self-help strategies. Primary outcome was H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
3
25
0
1
Order By: Relevance
“…However, this negative result is difficult to interpret given the absence of group differences in chronic stress levels in our UC cohort, indicating essentially normal perceived chronic stress in this sample despite elevated clinical symptoms of anxiety as quantified with the HADS. While sample characteristics of UC were in this respect similar to an earlier study in a different sample of UC that used a comparable recruitment strategy ( 75 ), other studies from our own group ( 76 ) and other groups [e.g., ( 63 )] reported more psychological impairment in patients, including elevated chronic stress levels. The lack of elevated chronic stress in this UC sample obviously limits the interpretation of these results, although owing to our approach to test the interaction this does not per se exclude an impact but rather a disease-specific differential association compared to controls.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, this negative result is difficult to interpret given the absence of group differences in chronic stress levels in our UC cohort, indicating essentially normal perceived chronic stress in this sample despite elevated clinical symptoms of anxiety as quantified with the HADS. While sample characteristics of UC were in this respect similar to an earlier study in a different sample of UC that used a comparable recruitment strategy ( 75 ), other studies from our own group ( 76 ) and other groups [e.g., ( 63 )] reported more psychological impairment in patients, including elevated chronic stress levels. The lack of elevated chronic stress in this UC sample obviously limits the interpretation of these results, although owing to our approach to test the interaction this does not per se exclude an impact but rather a disease-specific differential association compared to controls.…”
Section: Discussionsupporting
confidence: 71%
“…The lack of elevated chronic stress in this UC sample obviously limits the interpretation of these results, although owing to our approach to test the interaction this does not per se exclude an impact but rather a disease-specific differential association compared to controls. Clearly, our data do not provide conclusive answers, and hopefully inspire further study, possibly in selected patient groups presenting with higher stress levels or other impairment in psychological health, as recently accomplished by our group in a treatment trial ( 75 ), or in concert with biological measures relevant to neuroendocrine stress mediators and inflammation ( 76 ), both accomplished without concurrent brain imaging. Longitudinal studies already elucidated the relation between stress and disease course ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 84%
“…The present study presents long-term results of stress-related outcomes of a prospective RCT [ 25 ]. In addition, exploratory results of a sub-study applying a laboratory stress protocol conducted within the RCT are reported.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were randomized using computer generated stratified block randomization (Strata: sex and azathioprine) to either the lifestyle-modification group or the control group using the Random Allocation Software. For further information see Langhorst, Schöls [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation